Method for preparing cementing material and roadbed building material by hydrothermal activation of waste incineration fly ash

The method of preparing gelled materials through water thermal activation of waste incineration fly ash has been solved, and the problems of insufficient detoxification of various pollutants in the prior art are solved, and the problems of high-efficiency removal of heavy metals, chloride salts and dioxins are achieved, and high-performance roadbed building materials are prepared, with excellent environmental protection performance.

CN119874225APending Publication Date: 2025-04-25SHANGHAI UNIV +2

Patent Information

Application Number
CN202510059274.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing waste incineration fly ash resource treatment technology has problems such as insufficient detoxification of various pollutants, complex processes and high costs.

Method used

The method of preparing gelled materials through water-thermal activation of fly ash by waste incineration is used to prepare gelled materials by using hydrothermal high-temperature detoxification, hydrothermal gelled mineral phase precursor synthesis, and high-temperature activation. The process is simple, the cost is low, and the product detoxification effect is good.

Benefits of technology

It has achieved efficient dissolving and removal of heavy metals and chloride salts in waste incineration fly ash and efficient decomposition and removal of dioxins, and prepared high-performance road-based building materials, which has reduced the leaching amount of heavy metals and chlorine in the material, and has excellent environmental protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005242370800000051
    Figure BDA0005242370800000051
  • Figure BDA0005242370800000052
    Figure BDA0005242370800000052
  • Figure BDA0005242370800000053
    Figure BDA0005242370800000053
Patent Text Reader

Abstract

The invention relates to a method for preparing a cementing material through hydrothermal activation of waste incineration fly ash and a method for preparing a roadbed building material by using the cementing material, and belongs to the technical field of household waste resourceful treatment. The preparation method of the cementing material comprises the following steps: mixing 50-80% by mass of fly ash, 20-48% by mass of an auxiliary material and 0-2% by mass of an additive in a hydrothermal kettle, then adding water of which the mass is 2.5-3 times of the total mass of a solid material, fully and uniformly stirring, and carrying out hydrothermal reaction at 140-200 DEG C for 1-4 hours to obtain the cementing material. After cooling, carrying out solid-liquid separation to obtain a solid product and high-chlorine low-calcium wastewater, wherein the solid product is a gelling characteristic material precursor; and crushing, rinsing and granulating the solid, placing the granulated solid in a kiln, activating the granulated solid at a high temperature of 600-900 DEG C for 20-60 minutes, and cooling and crushing a sintered product to obtain the cementing material. The cementing material is prepared through hydrothermal high-temperature detoxification, hydrothermal gelation mineral phase precursor synthesis and high-temperature activation, and the method has the advantages of being simple in process, low in cost and good in product detoxification effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a technology for detoxifying waste incineration fly ash, and in particular to a method for preparing a cementitious material by hydrothermal activation of waste incineration fly ash, and a method for preparing roadbed building materials using the cementitious material, belonging to the technical field of resource treatment of domestic waste. Background Art

[0002] Fly ash from the incineration of domestic waste is a powdery fine-particle solid waste captured from the high-temperature incineration flue gas of domestic waste incineration power plants. It contains a large amount of heavy metals, dioxins and chloride salts, and is classified as hazardous waste HW 18. As of 2023, there are 964 waste incineration plants built in my country, with a disposal capacity of 1.035 million tons / day. Based on the 3% fly ash generation, about 11 million tons of fly ash are generated per year.

[0003] At present, the main method of treating and disposing fly ash from incineration in my country is still to solidify and stabilize it before safe landfill. However, with the steady progress of the country's waste-free city construction and the implementation of the "Technical Specifications for Pollution Control of Fly Ash from Incineration of Municipal Waste" (HJ 1134-2020), treatment and disposal technologies such as cement kiln co-treatment, high-temperature sintering of ceramsite, and high-temperature melting to prepare vitreous bodies have gradually become the mainstream of the market.

[0004] However, there are still some shortcomings in the implementation of the above technologies. For example, the co-treatment of cement kilns has strict requirements on the chlorine content of fly ash entering the kiln, and sufficient water washing, desalting and dechlorination treatment is required. The treatment of a large amount of high-concentration salt-containing wastewater after water washing requires the use of energy-intensive MVR salt separation technology, and the market prospects of the separated potassium and sodium salts are poor. The micropore structure of ceramsite during high-temperature sintering and high-temperature melting, the regulation of the melting point of the glass phase, the solidification of the heavy metal lattice, the separation of heavy metal chlorine-promoted volatilization, the treatment of highly enriched heavy metal secondary concentrated ash, and the pollutant risk control and resource application of sintering / melting products are all difficulties in the current application of related technologies.

[0005] In the prior art, such as Chinese invention patent CN116425508B (a method for preparing high-strength bricks using fly ash from garbage incineration and aluminum ash and its products), using raw materials containing aluminum ash and obtaining gel by electrolysis can realize the resource utilization of fly ash. However, a large amount of ammonia is produced during the electrolysis of aluminum ash. Although it can be absorbed by phosphoric acid solution, it increases equipment investment and operating costs, and is prone to leakage, resulting in serious hazards; secondly, when elemental aluminum comes into contact with air or water, it is easy to undergo a violent explosion and exothermic reaction. Although most of the aluminum in aluminum ash exists in the form of aluminum nitride, it is inevitable that unreacted elemental aluminum is wrapped inside the aluminum ash particles. During the electrolysis process, after the surface aluminum nitride is decomposed by the reaction, the elemental aluminum that may exist inside the aluminum ash particles directly contacts the aqueous solution, which may cause a violent reaction and pose a safety hazard. Finally, the aluminum ash electrolysis process has high energy consumption and requires the use of a large number of expensive ion exchange membranes, which makes this type of process have high energy consumption cost and large auxiliary material consumption, and is not suitable for large-scale industrial applications.

[0006] Therefore, there is an urgent need in the art to develop a waste incineration fly ash resource processing technology with lower cost, more environmental friendliness and low energy consumption. Summary of the invention

[0007] In order to solve the problems of insufficient detoxification of various pollutants in fly ash, complex process, high cost, etc. that are common in existing fly ash resource treatment technologies, this application proposes a method for preparing cementitious materials using fly ash from garbage incineration, and in order to consume solid waste-based cementitious materials in large quantities and fully activate the cementitious properties of the materials to prepare high-performance roadbed products, the present invention also proposes a method for preparing roadbed building materials using the prepared cementitious materials. The cementitious materials are prepared by utilizing hydrothermal high-temperature detoxification, hydrothermal gelling mineral phase precursor synthesis, and high-temperature activation, which has the characteristics of simple process, low cost, and good product detoxification effect.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a cementitious material by hydrothermal activation of waste incineration fly ash, comprising the following steps:

[0010] In terms of mass percentage, 50-80% fly ash, 20-48% auxiliary materials, and 0-2% additives are mixed in a hydrothermal kettle, wherein the amount of water added in the hydrothermal kettle is 2.5-3 times the total mass of the solid materials, and after being fully stirred, a hydrothermal reaction is carried out at a temperature of 140-200° C. for 1-4 hours, and after cooling, solid-liquid separation is performed to obtain a solid product and high-chloride and low-calcium wastewater, wherein the solid product is a precursor of a gelling characteristic material;

[0011] After the solid-liquid separation, the solid is crushed and rinsed 1-3 times, and then granulated, preferably with a particle size of 10-15 mm;

[0012] The particles are placed in a kiln and activated at a high temperature of 600-900° C. for 20-60 minutes. The sintered product is cooled and crushed to obtain a cementitious material.

[0013] By adopting the above method, during the high-temperature and high-pressure hydrothermal process of fly ash, soluble heavy metals and chloride salts are fully released into the hydrothermal solution, thereby achieving the separation of pollutants from the solid phase of fly ash. At the same time, under the high-temperature and high-pressure hydrothermal conditions, after the fly ash and auxiliary materials are combined, a mineral phase precursor with gelling properties can be generated, and calcium can be effectively fixed in the solid phase, inhibiting the dissolution and release of calcium into the water body. The solid materials separated by solid-liquid separation after hydrothermal treatment are rinsed in multiple stages to ensure the full removal of heavy metals and chloride salts in the solid materials. During the high-temperature activation process, the mineral phase precursor with gelling properties undergoes dehydration, condensation and other reactions to generate a mineral phase material with strong gelling properties. After crushing and grinding, it can be used as a roadbed building material.

[0014] Preferably, the auxiliary material is a material containing silicon and aluminum components, including but not limited to natural minerals / ores, soil, various industrial solid byproducts / solid wastes, such as aluminum ash, fly ash, etc. In the auxiliary material, there is no strict requirement for the mass ratio of silicon to aluminum, and it is only required that the mass of silicon is higher than that of aluminum, which helps to preferentially generate a mineral phase dominated by silicates during the water washing process, and simultaneously form aluminosilicates and aluminates, thereby optimizing the mineral conversion process, improving the stabilization effect on harmful components in fly ash, and facilitating resource utilization.

[0015] Preferably, the additive is a reaction promoting activator, including but not limited to alkali, calcium salt, iron salt, aluminum salt, etc., such as lime. For example, adding lime can not only provide calcium required for the formation of calcium silicate series mineral phases, but also adjust the alkalinity; if iron salt and aluminum salt are added, it can guide the formation of silicate, aluminate and other mineral phases in the system.

[0016] In a second aspect of the present invention, there is provided a method for preparing roadbed building materials using the cementitious material, comprising the following steps:

[0017] According to the percentage by mass, 70-90% of the gelling material, 0-10% of the active stimulating material, 5-10% of the dehydrating agent, and 5-10% of the additive are mixed with 15-40% of the solid mass of water to prepare a semi-finished roadbed brick. Or after high-pressure molding at 5-30MPa, the semi-finished roadbed brick is placed in an autoclave at 120-250°C for autoclaving for 1-10 hours to prepare a semi-finished roadbed brick. Preferably, the semi-finished roadbed brick is reacted at 5-20MPa and 140-220°C for 2-6 hours to prepare a semi-finished roadbed brick. After the semi-finished roadbed brick or the semi-finished autoclaved brick is cured for 1-10 days at 0-40°C and a relative humidity of 70-100%, a finished roadbed brick or a finished autoclaved brick is obtained.

[0018] Preferably, the active stimulating material is mainly silicon-containing or aluminum-containing material, including but not limited to fly ash, silicon oxide, silica powder, sand, aluminum ash, bauxite, cement, etc. The purpose of adding the active stimulating material is that when preparing the finished roadbed building materials, these materials hydrate to produce gelling properties faster, providing early strength of the roadbed material.

[0019] Preferably, the dehydrating agent is lime, etc. The main function of the dehydrating agent is to absorb / lock free water when adding water to mix and make slurry, usually by using the water-absorbing property of lime to accelerate the drying speed of the slurry and advance the initial setting time.

[0020] Preferably, the additive is gypsum, etc. The addition of the gypsum additive helps to produce a synergistic effect with other components, increases the viscosity of the mixture after slurrying, and also helps to improve the early strength of the newly formed roadbed material.

[0021] This application has the following beneficial effects:

[0022] The present application realizes the efficient dissolution and removal of heavy metals and chloride salts and the efficient decomposition and removal of dioxins in the hydrothermal process of waste incineration fly ash. In the hydrothermal detoxification process, the silica-alumina components introduced by the compatibility are used to generate a gelling characteristic mineral phase precursor. The gelling characteristic mineral phase precursor is activated by high-temperature activation to stimulate the gelling property, thereby realizing a feasible technical solution for preparing gelling materials from waste incineration fly ash.

[0023] During the hydrothermal high temperature and high pressure process, the chloride salt solubility enhancement and diffusion effect are utilized to promote the dissolution of chloride salt in fly ash from the solid phase to the liquid phase. At the same time, under the hydrothermal high temperature and high pressure environment, the calcium in the fly ash reacts with the silicon and aluminum components in the auxiliary materials to form a calcium silicon aluminum system mineral phase. In the process of preparing roadbed building materials with the cementitious materials obtained by medium temperature activation, the lime quickly absorbs the free water in the slurry during the hydration process, promotes the formation of cementitious hydration products, and reduces the initial setting time of the roadbed building materials; gypsum reacts with water to form calcium sulfate dihydrate crystals, which improves the initial setting strength of the material. In addition, the composite action of lime and gypsum not only promotes the formation of hydration products through chemical reactions, but also further enhances the viscosity and stability of the slurry by optimizing the particle distribution and microstructure of the slurry. Ultimately, this synergistic effect greatly reduces the leaching of heavy metals and chlorine in the material, so that the prepared roadbed material has excellent environmental performance while meeting high performance requirements.

[0024] The present application achieves the full dissolution and separation of chloride salts in waste incineration fly ash, and at the same time inhibits the dissolution of calcium in the fly ash into the liquid phase by generating a calcium-silicon-aluminum system mineral phase through the calcium in the fly ash and the silicon-aluminum components in the auxiliary materials, thereby greatly reducing the treatment cost of fly ash desalination wastewater. DETAILED DESCRIPTION

[0025] The following examples and comparative examples are used to further describe the specific embodiments of the present invention. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0026] Example 1

[0027] A method for preparing a cementitious material by hydrothermal activation of waste incineration fly ash, comprising the following steps:

[0028] In terms of mass percentage, 65% fly ash and 35% fly ash (SiO2 is 40%, Al2O3 is 35%, and the rest is 25%) are mixed in a hydrothermal kettle, and the amount of water added in the hydrothermal kettle is 3 times the total mass of the solid materials. After being fully stirred, the hydrothermal reaction is carried out at a temperature of 160°C for 4 hours, and after cooling, the solid-liquid separation is carried out to obtain the precursor of the gelling characteristic material and the wastewater. The chlorine content in the wastewater is 3.7%, and the calcium ion concentration is 6231mg / L.

[0029] After solid-liquid separation, the solid is crushed and rinsed twice, and then granulated to a particle size of 10-15 mm. The particles are placed in a kiln and activated at 700°C for 20 minutes. The sintered product is cooled and crushed to obtain a gelled material.

[0030] As shown in Table 1, the heavy metal leaching (HJ 557), dioxin content, and soluble chlorine content of the cementitious material meet the HJ1134 standard, and the cementitious performance meets the requirements related to the strength activity index in GB / T 1596.

[0031] Table 1 Pollutant indexes of cementitious materials

[0032]

[0033] Further, the roadbed material is prepared by using the above-mentioned cementitious material, comprising the following steps:

[0034] According to the mass percentage, 80% cementitious material, 10% fly ash, 5% lime and 5% gypsum are mixed with 40% water of solid mass for slurry mixing and injection molding to prepare semi-finished roadbed bricks. After curing for 7 days at about 10°C and 70% humidity, the finished roadbed bricks are obtained.

[0035] The 7-day compressive strength of the finished roadbed brick is 15.2MPa, the 14-day compressive strength is 18.9MPa, and the 28-day compressive strength is 22.1MPa. The heavy metal leaching test was carried out according to standard HJ 577, and the results met the relevant requirements of standard HJ 1134. The dioxin content and soluble chloride salts met the relevant requirements of standard HJ 1134, and the relevant test results are shown in Table 2.

[0036] Table 2 Product contamination index test results

[0037]

[0038] Example 2

[0039] A method for preparing a cementitious material by hydrothermal activation of waste incineration fly ash, comprising the following steps:

[0040] In percentage, 50% fly ash, 48% fly ash (SiO2 is 53%, Al2O3 is 28%, and the rest is 19%), and 2% lime are mixed in a hydrothermal kettle, and the amount of water added in the hydrothermal kettle is 2.5 times the total mass of the solid materials. After being fully stirred, the hydrothermal reaction is carried out at 140°C for 3 hours, and after cooling, the solid-liquid separation is carried out to obtain the precursor of the gelling characteristic material and the wastewater. The chlorine content in the wastewater is 4.2%, and the calcium ion concentration is 7346mg / L.

[0041] After solid-liquid separation, the solid is crushed and rinsed twice, and then granulated to a particle size of 10-15 mm. The particles are placed in a kiln and activated at 600°C for 25 minutes. The sintered product is cooled and crushed to obtain a gelled material.

[0042] As shown in Table 3, the heavy metal leaching (HJ 577), dioxin content, and soluble chlorine content of the cementitious material meet the HJ1134 standard, and the cementitious performance meets the requirements related to the strength activity index in GB / T 1596.

[0043] Table 3 Contaminant indexes of cementitious materials

[0044]

[0045]

[0046] Further, the roadbed material is prepared by using the above-mentioned cementitious material, comprising the following steps:

[0047] According to the percentage by mass, 85% of cementitious material, 5% of silica powder, 5% of lime and 5% of gypsum are formed by high pressure at 20MPa and then autoclaved in an autoclave at 180°C for 6 hours to prepare an autoclaved brick semi-finished product. The autoclaved brick semi-finished product is cured for 5 days at 15°C and 100% humidity to obtain an autoclaved brick finished product.

[0048] The compressive strength of the finished autoclaved brick is 22.9MPa after 7 days, 32.5MPa after 14 days, and 38.6MPa after 28 days. The heavy metal leaching test was carried out according to standard HJ 577, and the results met the relevant requirements of standard HJ 1134. The dioxin content and soluble chloride salts met the relevant requirements of standard HJ 1134, and the relevant test results are shown in Table 4.

[0049] Table 4 Product contamination index test results

[0050]

[0051] Example 3

[0052] A method for preparing a cementitious material by hydrothermal activation of waste incineration fly ash, comprising the following steps:

[0053] In terms of mass percentage, 80% fly ash and 20% fly ash (SiO2 is 58%, Al2O3 is 31%, and the rest is 11%) are mixed in a hydrothermal kettle, and the amount of water added in the hydrothermal kettle is 3 times the total mass of the solid materials. After being fully stirred, the hydrothermal reaction is carried out at a temperature of 170°C for 3 hours, and after cooling, the solid-liquid separation is carried out to obtain a gelling characteristic material precursor and wastewater. The chlorine content in the wastewater is 3.5%, and the calcium ion concentration is 7896mg / L.

[0054] After solid-liquid separation, the solid is crushed and rinsed twice, and then granulated to a particle size of 10-15 mm. The particles are placed in a kiln and activated at 750°C for 25 minutes. The sintered product is cooled and crushed to obtain a gelled material.

[0055] As shown in Table 5, the heavy metal leaching (HJ 557), dioxin content, and soluble chlorine content of the cementitious material meet the HJ1134 standard, and the cementitious performance meets the requirements related to the strength activity index in GB / T 1596.

[0056] Table 5 Pollutant indexes of cementitious materials

[0057]

[0058] Further, the roadbed material is prepared by using the above-mentioned cementitious material, comprising the following steps:

[0059] According to the mass percentage, 80% cementitious material, 10% fly ash, 5% lime and 5% gypsum are mixed with 30% water of solid mass for slurry mixing and injection molding to prepare semi-finished roadbed bricks. After curing for 10 days at about 0°C and 80% humidity, the finished roadbed bricks are obtained.

[0060] The 7-day compressive strength of the finished roadbed brick is 16.4MPa, the 14-day compressive strength is 21.7MPa, and the 28-day compressive strength is 25.8MPa. The heavy metal leaching test was carried out according to standard HJ 577, and the results met the relevant requirements of standard HJ 1134. The dioxin content and soluble chloride salts met the relevant requirements of standard HJ 1134, and the relevant test results are shown in Table 6.

[0061] Table 6 Product contamination index test results

[0062]

[0063] Example 4

[0064] A method for preparing a cementitious material by hydrothermal activation of waste incineration fly ash, comprising the following steps:

[0065] In terms of mass percentage, 70% fly ash and 30% fly ash (SiO2 is 52%, A12O3 is 27%, and others account for 21%) are mixed in a hydrothermal kettle, and the amount of water added in the hydrothermal kettle is 2.5 times the total mass of the solid materials. After being fully stirred, the hydrothermal reaction is carried out at a temperature of 200°C for 1 hour, and after cooling, the solid-liquid separation is carried out to obtain the precursor of the gelling characteristic material and the wastewater. The chlorine content in the wastewater is 4.1%, and the calcium ion concentration is 8930mg / L.

[0066] After solid-liquid separation, the solid is crushed and rinsed once, and then granulated to a particle size of 10-15 mm. The particles are placed in a kiln and activated at 900°C for 20 minutes. The sintered product is cooled and crushed to obtain a gelled material.

[0067] As shown in Table 7, the heavy metal leaching (HJ 557), dioxin content, and soluble chlorine content of the cementitious material meet the HJ1134 standard, and the cementitious performance meets the requirements related to the strength activity index in GB / T 1596.

[0068] Table 7 Contaminant indexes of cementitious materials

[0069]

[0070] Further, the roadbed material is prepared by using the above-mentioned cementitious material, comprising the following steps:

[0071] According to the mass percentage, 90% cementitious material, 5% lime and 5% gypsum are formed by 5MPa high pressure and then autoclaved in an autoclave at 220°C for 2 hours to prepare autoclaved brick semi-finished products. After curing for 7 days at about 25°C and 90% humidity, the autoclaved brick finished products are obtained.

[0072] The compressive strength of the finished autoclaved brick is 17.8MPa after 7 days, 22.1MPa after 14 days, and 27.9MPa after 28 days. The heavy metal leaching test was carried out according to standard HJ 577, and the results met the relevant requirements of standard HJ 1134. The dioxin content and soluble chloride salts met the relevant requirements of standard HJ 1134, and the relevant test results are shown in Table 8.

[0073] Table 8 Product contamination index test results

[0074]

[0075] Example 5

[0076] A method for preparing a cementitious material by hydrothermal activation of waste incineration fly ash, comprising the following steps:

[0077] In terms of mass percentage, 75% fly ash and 25% fly ash (SiO2 is 51%, Al2O3 is 27%, and the rest is 22%) are mixed in a hydrothermal kettle, and the amount of water added in the hydrothermal kettle is 3 times the total mass of the solid materials. After being fully stirred, the hydrothermal reaction is carried out at a temperature of 180°C for 2 hours, and after cooling, the solid-liquid separation is carried out to obtain the precursor of the gelling characteristic material and the wastewater. The chlorine content in the wastewater is 3.5%, and the calcium ion concentration is 6797mg / L.

[0078] After solid-liquid separation, the solid is crushed and rinsed once, and then granulated to a particle size of 10-15 mm. The particles are placed in a kiln and activated at 800°C for 60 minutes. The sintered product is cooled and crushed to obtain a gelled material.

[0079] As shown in Table 9, the heavy metal leaching (HJ 557), dioxin content, and soluble chlorine content of the cementitious material meet the HJ1134 standard, and the cementitious performance meets the requirements related to the strength activity index in GB / T 1596.

[0080] Table 9 Pollutant indexes of cementitious materials

[0081]

[0082] Further, the roadbed material is prepared by using the above-mentioned cementitious material, comprising the following steps:

[0083] According to the mass percentage, 70% of cementitious material, 10% of cement, 10% of lime and 10% of gypsum are mixed with 15% of water by solid mass for slurry mixing and injection molding to prepare semi-finished roadbed bricks. After curing for 1 day at about 40° C. and 70% humidity, the finished roadbed bricks are obtained.

[0084] The 7-day compressive strength of the finished roadbed brick is 13.7MPa, the 14-day compressive strength is 19.6MPa, and the 28-day compressive strength is 27.2MPa. The heavy metal leaching test was carried out according to standard HJ 577, and the results met the relevant requirements of standard HJ 1134. The dioxin content and soluble chloride salts met the relevant requirements of standard HJ 1134, and the relevant test results are shown in Table 10.

[0085] Table 10 Product contamination index test results

[0086]

[0087] Comparative Example 1

[0088] This comparative example provides a method for preparing a cementitious material from waste incineration fly ash, and its raw material ratio is exactly the same as that of Example 1, except that the hydrothermal reaction temperature is 100°C.

[0089] The comparative example product was tested for heavy metal leaching according to the HJ 577 method, and the leaching concentrations of heavy metals Pb and Cd reached 1.9 mg / L and 0.2 mg / L, respectively, exceeding the relevant requirements of the HJ 1134 standard.

[0090] Comparative Example 2

[0091] This comparative example provides a method for preparing a cementitious material from waste incineration fly ash, and its raw material ratio is exactly the same as that of Example 1, except that the high-temperature activation temperature is 300°C.

[0092] The dioxin content of the comparative product was detected to be 68 ng-TEQ / kg. According to the HJ 577 method, the heavy metal leaching was tested, and the leaching concentrations of heavy metals Zn and Pb were 2.4 mg / L and 1.7 mg / L respectively, exceeding the relevant requirements of the HJ 1134 standard.

[0093] Comparative Example 3

[0094] This comparative example provides a method for preparing a cementitious material from waste incineration fly ash, and its test parameters are exactly the same as those in Example 1, except that the raw material ratio is 100% waste incineration fly ash and the auxiliary material ratio is 0%.

[0095] The gelling performance (strength activity index) of the comparative product was only 58% according to the requirements of GB / T 1596, which does not meet the requirement of ≥70% in the standard. In addition, the heavy metal leaching was tested according to the HJ 577 method, and the leaching concentrations of heavy metals Zn and Pb reached 2.1 mg / L and 1.3 mg / L respectively, exceeding the relevant requirements of the HJ 1134 standard.

[0096] Comparative Example 4

[0097] This comparative example provides a method for preparing a roadbed material using a cementitious material. The cementitious material used is the same as that in Example 1. The method for preparing the roadbed material is basically the same as that in Example 1, except that the cementitious material is 100% without adding any auxiliary materials.

[0098] The product obtained in this comparative example has a 7-day compressive strength of 12.9 MPa, a 14-day compressive strength of 12.5 MPa, and a 28-day compressive strength of 18.6 MPa. The performance is poor and the application is limited. In addition, according to the HJ 577 method, the heavy metal leaching concentration of the product Zn reaches 2.9 mg / L, which exceeds the relevant requirements of the HJ 1134 standard.

[0099] Comparative Example 5

[0100] This comparative example provides a method for preparing a roadbed material with a cementitious material. The preparation method is basically the same as that of Example 2, except that the cementitious material in the mix is ​​completely replaced by fly ash.

[0101] The product obtained in this comparative example has a 7-day compressive strength of 13.2 MPa, a 14-day compressive strength of 15.1 MPa, and a 28-day compressive strength of 19.2 MPa, and its strength performance is significantly lower than that of the products in Examples 1 and 2.

[0102] Comparative Example 6

[0103] This comparative example provides a method for preparing a roadbed material with a cementitious material. The preparation method is basically the same as that of Example 2, except that the cementitious material in the mix is ​​replaced by a powder material obtained by directly calcining waste incineration fly ash at 700°C.

[0104] The 7-day compressive strength obtained in this comparative example is 8.9 MPa, the 14-day compressive strength is 9.5 MPa, and the 28-day compressive strength is 12.5 MPa, and the strength performance is significantly lower than that of the cementitious material used in the present invention.

Claims

1. A method for preparing a cementitious material by hydrothermal activation of waste incineration fly ash, characterized in that: The following steps are involved: In terms of mass percentage, 50-80% fly ash, 20-48% auxiliary materials, and 0-2% additives are mixed in a hydrothermal kettle, wherein the amount of water added in the hydrothermal kettle is 2.5-3 times the total mass of the solid materials, and after being fully stirred, a hydrothermal reaction is carried out at a temperature of 140-200° C. for 1-4 hours, and after cooling, solid-liquid separation is performed to obtain a solid product and high-chloride and low-calcium wastewater, wherein the solid product is a precursor of a gelling characteristic material; After the solid-liquid separation, the solid is crushed and rinsed 1-3 times before being granulated; The particles obtained after the granulation treatment are placed in a kiln and activated at a high temperature of 600-900° C. for 20-60 minutes. The sintered product is cooled and crushed to obtain a gelled material.

2. The method for preparing a cementitious material by hydrothermal activation of waste incineration fly ash according to claim 1, characterized in that: The auxiliary material is a material containing silicon and aluminum components, and in the auxiliary material, the mass of silicon is greater than the mass of aluminum.

3. The method for preparing a cementitious material by hydrothermal activation of waste incineration fly ash according to claim 2, characterized in that: The auxiliary material is fly ash.

4. The method for preparing a cementitious material by hydrothermal activation of waste incineration fly ash according to claim 1, characterized in that: The additive is lime.

5. The method for preparing a cementitious material by hydrothermal activation of waste incineration fly ash according to claim 1, characterized in that: The particle size is 10-15 mm.

6. A method for preparing roadbed building materials, characterized in that: The following steps are involved: According to the percentage by mass, 70-90% of the cementitious material prepared by the method according to any one of claims 1 to 5, 0-10% of the active stimulating material, 5-10% of the dehydrating agent, and 5-10% of the additive are mixed with 15-40% of the solid mass of water to make a slurry injection molding to prepare a semi-finished roadbed brick, or after being subjected to 5-30MPa high pressure molding and then placed in an autoclave at 120-250°C for autoclaving for 1-10 hours to prepare a semi-finished autoclaved brick; the semi-finished roadbed brick or the semi-finished autoclaved brick is cured for 1-10 days at 0-40°C and a relative humidity of 70-100% to obtain a finished roadbed brick or a finished autoclaved brick.

7. The method for preparing roadbed building materials according to claim 6, characterized in that: The high pressure forming conditions are: 5-20MPa, 140-220°C, autoclaving reaction for 2-6 hours to prepare autoclaved brick semi-finished products.

8. The method for preparing roadbed building materials according to claim 6, characterized in that: The active excitation material is a silicon-containing or aluminum-containing material.

9. The method for preparing roadbed building materials according to claim 8, characterized in that: The active stimulating material is selected from fly ash, silica powder and cement.

10. The method for preparing roadbed building materials according to claim 6, characterized in that: The dehydrating agent is lime; the additive is gypsum.

Citation Information

Patent Citations

  • A method for preparing high-strength bricks using fly ash and aluminum ash from waste incineration, and the resulting products.

    CN116425508B

Cited By

  • Method for promoting dissolution and dechlorination of waste incineration fly ash and inhibiting calcium dissolution

    CN122322232A